Kepuasan Siswa terhadap Pembelajaran Daring Menggunakan Microsoft Teams dan Video Youtube pada Materi Program Linier - Wachid Nugroho (Jurnal THEOREMS (The Original Research of Mathematics), 2021)
This study aims to describe the level of satisfaction of class X students of SMK Negeri 2 Salatiga with the use of Microsoft Teams and YouTube videos as a means of online learning on linear program material. This research is a qualitative research. Data were collected through: 1) filling out a questionnaire regarding the level of student satisfaction with media use, media accessibility, interactive nature of learning, understanding of material, achievement of learning outcomes, and remedial or enrichment services; and 2) whatsapp conversation to complete the questionnaire data. The questionnaire data were analyzed descriptively to obtain a category of student satisfaction levels and confirmed by whatsapp conversation data. The results of the research were the level of student satisfaction in all categories, namely 1) media use; 2) media accessibility; 3) the interactive nature of learning; 4) understanding of the material; 5) achievement of learning outcomes; and 6) remedial or enrichment services are in the satisfied category.Keywords: student satisfaction, microsoft teams, online learning, linear programming, youtube video